Adaptation of Moringa Leaf Extract on Hemoglobin and Arm Circumference in Adolescent Girls Semarang - Sri Achadi Nugraheni; Ari Yuniastuti; Suryani As’ad; Pingkan Fristiwi; Fatimah Asri Fadhilah Aulia; Shafa Alya Kamila (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Adolescent malnutrition, particularly anemia, remains a major public health challenge in developing countries, including Indonesia, as it increases the risk of growth retardation, developmental disorders, poor pregnancy outcomes, and infectious diseases. Nutritional interventions during adolescence are crutial for improving health and breaking the intergenerational cycle of malnutrition. This study aimed to analyze the effect of Moringa oleifera capsules on hemoglobin (Hb) levels and Mid-Upper Arm Circumference (MUAC) among adolescent girls in Semarang. A quasi-experimental study with a pretest–posttest control group design was conducted in two junior high schools in Semarang (SMPN 39 and SMPN 8), involving 102 female students aged 13–15 years, who were selected using purposive sampling. Participants were assigned to an intervention group (n = 51) receiving 300 mg of Moringa oleifera capsules twice weekly for 6 months under teacher supervision, and a control group (n = 51) receiving no supplementation. Data were collected at baseline and after the intervention, including Hb measurement (Hemocue analyzer) and MUAC. Data were analyzed using paired t-tests and independent t-tests. Results showed a significant improvement in Hb levels in the intervention group (mean pretest 11.58±0.87 g/dL; posttest 13.65±0.89 g/dL; p<0.001), whereas no significant change was found in the control group (p = 0.132). MUAC also increased significantly in the intervention group (pretest 25.50±4.06 cm; posttest 26.21±4.94 cm; p = 0.002), with a greater improvement compared to the control group (p = 0.002). In conclusion, supplementation with Moringa oleifera effectively improved Hb levels and MUAC among adolescent girls. This intervention has potential as a practical and affordable strategy for preventing anemia and improving nutritional status in adolescents.